Five-Decade Update on Chemopreventive and Other Pharmacological Potential of Kurarinone: a Natural Flavanone - Kumar, Shashank; Prajapati, Kumari Sunita; Shuaib, Mohd; Kushwaha, Prem Prakash; Tuli, Hardeep Singh; Singh, Atul Kumar (Frontiers in Pharmacology, 2021)
In the present article we present an update on chemoprevention role and other pharmacological activities reported on Kurarinone, a natural flavanone (from 1970 to 2021). To the best of our knowledge this is the first and exhaustive review of Kurarinone. The literature was obtained from different search engines platforms including PubMed. The Kurarinone possesses anticancer potential against cervical, lung (non small and small), hepatic, esophageal, breast, gastric, cervical, and prostate cancer cells. In vivo anticancer potential of Kurarinone has been extensively studied in lungs (non-small and small) using experimental xenograft models. In in vitro anticancer studies, Kurarinone showed IC50 in the range of 2-62 µM while in vivo efficacy was studied in the range of 20-500 mg/kg body weight of the experimental organism. The phytochemical showed higher selectivity towards cancer cells in comparison to respective normal cells. Kurarinone inhibits cell cycle progression in G2/M and Sub-G1 phase in a cancer-specific context. It induces apoptosis in cancer cells by modulating molecular players involved in apoptosis/anti-apoptotic processes such as NF-κB, caspase 3/8/9/12, Bcl2, Bcl-XL, etc. The phytochemical inhibits metastasis in cancer cells by modulating the protein expression of Vimentin, N-cadherin, E-cadherin, MMP2, MMP3, and MMP9. It produces a cytostatic effect by modulating p21, p27, Cyclin D1, and Cyclin A proteins in cancer cells. Kurarinone possesses stress-mediated anticancer activity and modulates STAT3 and Akt pathways. Besides, the literature showed that Kurarinone possess anti-inflammatory, anti-drug resistance, anti-microbial (fungal, yeast, bacteria, and Coronavirus), channel and transporter modulation, neuroprotection, and estrogenic activities as well as tyrosinase/diacylglycerol acyltransferase/glucosidase/aldose reductase/human carboxylesterases 2 inhibitory potential. Kurarinone also showed therapeutic potential in the clinical study. Further, we also discussed the isolation, bioavailability, metabolism and toxicity of Kurarinone in experimental models.